A Preliminary Diffusion Tensor Imaging Study: Analysis of Whole Brain according to the Affected Side in Tinnitus - Shrestha, L. (Nepalese Journal of Radiology, 2017)
Aim: To investigate the role of white matter integrity in the pathophysiology of tinnitus, and also to analyze the whole brain for white matter changes quantitatively by comparing tinnitus patients with healthy controls based on the affected side of the tinnitus using Tract Based Spatial Statistics (TBSS). Methods: Total of 41 right-handed tinnitus patients and 35 age-matched right-handed healthy controls were initially examined non-invasively in resting-state using the 3.0T MRI scanner. We obtained the estimated Fractional anisotropy (FA), mean diffusivity (MD), Axial Diffusivity (AD), Radial Diffusivity (RD), and Mode of Anisotropy (MO) data for each subject. TBSS was used to perform group statistical analysis of DTI data from each group. Results: Compared to controls in right-sided tinnitus patients, FA and MO were decreased, and MD was normal with decreased AD and increased RD. FA and AD showed similar decreased values (t>1.5, FWEcorrected P<0.05) in the right corticospinal tract, right superior longitudinal fasciculus, and right inferior fronto-occipital fasciculus. Compared to controls with left-sided tinnitus patients, FA and MO were decreased, and MD was also increased with decreased AD with increased RD in patients. MO showed significantly decreased values (t>1.5, FWEcorrected P<0.05) of MO in Forceps major, bilateral cingulum (especially the left), and bilateral anterior thalamic radiation. Bilaterally affected tinnitus patients showed no difference when compared to controls. Conclusion: After analyzing the whole brain for white matter changes quantitatively using TBSS, changes were observed in unilaterally affected tinnitus patients compared to controls. Our findings indicated cross-modal plasticity could have caused changes in somatosensory, audio-visual, limbic, and attention pathways. Nepal Journal of Radiology Vol.5(1-2) 2015: 1-12